Hubungan Perencanaan Pajak dan Pengungkapan Pajak pada Perusahaan Terbuka di BEI - Kennardi Tanujaya; Catherine Catherine (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2023)
This study aims to determine the impact of tax planning on tax disclosure. The approach used in this study is a quantitative approach using data on the financial statements of non-financial companies listed on the Indonesia Stock Exchange from 2017 to 2021. The results showed that tax planning had a significant negative effect on tax disclosure. This shows that the tax planning of the company is not comparable with the disclosures made by the company which results in reduced transparency of reports in a company. That way, the more aggressive tax planning will reduce tax disclosure in the company's financial statements.